Projecting the Implementation Feasibility of CLIL Approach for TEYL at Primary Schools in Indonesia - Setyaningrum, Rina Wahyu; Purwati, Oikurema (Universitas Muhammadiyah Sidoarjo, 2020)
2013 curriculum of Indonesia has amended English as an extra-curricular or a local content subject at primary schools. There are no standards to achieve and the teachers have to find the appropriate strategies to its delivery. It triggers the teachers’ lack of confidence in terms of content and methods. On the other hand, cognitive domain with the test as achievement standard regardless providing the experience of using the language for communication has been practiced. Integrating the thematic units of primary schools’ thematic lesson seems possible to carry out because the teacher can use its themes or sub-themes as a topic for Teaching English to Young Learners (TEYL). This exploratory case study employs in-depth interviews with three teachers from well-established schools using a semi-structured interview, observations for field notes, and focus group discussion. The findings reveal that all teachers developed the materials for their teaching based on the regular class thematic lessons and a book provided by the local government. As for teaching practice, they have implemented the CLIL principles although they did not realize it. Ultimately, CLIL adaptation is appropriate for TEYL as that representative area in as much as teacher’s English language proficiency and pedagogical competency are upgraded. Highlights: Teaching English to Young Learners (TEYL) should provide the young learners opportunities to use the English language contextually. Soft CLIL does not require a high level of achievement in language but it provides the students simple language instruction with simplified materials.